The effect of platelet rich concentrate on the regenerative capacity of mesenchymal stromal cells and its potential application in cartilage repair / Shani Samuel - Shani, Samuel (2017)
The use of regenerative promoters such as mesenchymal stromal cells (MSC) constitutes one of the novel approaches to enhance tissue repair. However, these cells need to be greatly expanded and differentiated prior to their clinical use. Platelet rich concentrate (PRC) has recently emerged as a potentially valuable adjunct that could considerably enhance the therapeutic potential of MSC. Although there are several lines of evidence indicating that PRC enhanced proliferation and differentiation of MSC when combined with lineage-specific culture media, the extent of contribution of the platelet itself has not been previously demonstrated. This thesis aimed to investigate the effect of PRC in serum free medium (without the influence of additional differentiation media) in enhancing the proliferation and differentiation capacity of MSC in vitro and their regenerative potential to repair focal cartilage defect in vivo. The first study involved optimisation of PRC preparation and investigating the effect of a single application of PRC in inducing the proliferation and differentiation of human bone marrow-derived MSC (hMSC) within a very short time span. The results showed that hMSC proliferation was greatest when the cells were cultured in medium containing 15% PRC. At this optimal dose, PRC was able to induce hMSC differentiation to the common mesenchymal lineages i.e. osteogenic, adipogenic and chondrogenic, within 8 days of culture duration, without the need to be activated and the aid of any external lineage-specific growth factors in the culture medium. The study was further extended to compare the expression of lineage-specific markers both at the mRNA and protein levels of cells undergoing osteogenesis, adipogenesis and chondrogenesis under the influence of PRC to those cultured in the standard lineage-specific differentiation media during 24 days of culture (i.e. typical duration to achieve complete cellular differentiation to the common mesenchymal lineages). The results indicate that PRC induced osteogenesis and chondrogenesis at a iv greater extent compared to the respective standard differentiation media. Chondrogenic hMSCs in the PRC group showed lower expression of hypertrophic genes. The final study was conducted to determine the applicability and the potential advantageous role of PRC in promoting chondrogenesis of MSC in vivo to enhance cartilage repair in a rabbit model of focal cartilage defect. Rabbits (6-7 months old) were subjected to full thickness focal cartilage defects limited to the chondral surface. At 3 and 6 month post-transplantation, animals in the PRC+allogenic rabbit MSC (rbMSC) group had significantly higher morphological score (ICRS) and histological score (O’Driscoll) compared to rbMSC and PRC group alone. Strong safranin O and collagen type II staining and high glycosaminoglycan content confirmed the formation of a hyaline-like cartilage in the PRC+rbMSC group. Collectively, these results demonstrate that PRC alone in serum free medium enhanced MSC regenerative capacity both in vitro and in vivo. PRC on its own could be used as an adjunct to provide sufficient pool of pre-differentiated MSC for potential clinical application in musculoskeletal tissue regeneration, particularly for the repair of focal cartilage injury